Text Analysis Study on Urban farming News Toward Food Security in Indonesia: Sentiment Analysis, Named Entity Recognition, Topic Modelling, and Social Network Analysis - Dewi Krismawati; Satria Bagus Panuntun (Politeknik Statistika STIS, 2023)
Urban farming is an increasingly popular trend in agricultural activities. Urban farming is an attempt to achieve urban sustainability from an environmental, social and economic perspective. In order to understand the phenomenon of urban farming in society, one of the media used is a news portal. This research aims to gain an in-depth understanding of community perceptions, social networks and issues related to the urban farming phenomenon. Data was collected using the web-scraping method on three national news portals in Indonesia. Data analysis was carried out using sentiment analysis, NER, topic modelling and social network analysis methods. Sentiment analysis shows that there is a generally positive sentiment towards urban farming. Government officials and environmental activists are frequently mentioned as supporting and promoting urban agriculture. Social network analysis reveals interactions between government agencies, non-governmental organisations and the media. The relationships between these stakeholders form a network that plays a role in building awareness, cooperation and knowledge exchange to strengthen food security through urban agriculture.